O vibrato na flauta transversal: análise da forma da onda - Rodrigo Manoel Frade (2018)
This research investigates the frequency fluctuation contour produced by the use of vibrato on the flute. Samples of notes with vibrato were recorded by 16 flutists, of whom 5 were professionals and 11 were undergraduate students at the School of Music at the Federal University of Minas Gerais. Each participant recorded six long notes with vibrato on low, medium, and high registers of the instrument, totaling 96 samples. The samples were analyzed using PRAAT software. Six major trends were identified in the shape of the vibrato wave on the flute: sine, triangular, trapezoidal, shorter aclive than slope, longer aclive than slope, and peaks at the base of the wave. The different waveforms observed by the present research constitute a further step towards the understanding the sound specificities of each flute player.